PENGARUH DEWAN KOMISARIS DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERBANKAN - Puspa Fadila; Imam Ghozali (Diponegoro Journal of Accounting, 2016)
This study aims to analyze the factors that affect to the banking company's performance in Indonesia. Measurements for the banking company's performance using Tobin’s Q formula.Object in this study are banking companies that are listed in the Indonesia Stock Exchange and always conduct financial reporting and assessed its annual report in 2011-2014. Data used is secondary data, such as financial statements and annual reports. Analysis of the data used is descriptive statistics, the classic assumption test, and regression analysis. The results of this study showed that the board size, board activity, institutional ownership, and foreign ownership are significantly affect to the banking company's performance in Indonesia.